2010
DOI: 10.29309/tpmj/2010.17.04.3034
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Selection of Nursing Profession in Pakistan

Abstract: Nursing is the backbone of health care delivery system. There are various factors which influence the choice of selecting nursing as profession. Objectives: (1) To find out the socio demographic profile of nurses working at Ghurki Trust Teaching Hospital (GTTH) Lahore. (2) To explore the reasons for selection of this profession. Study design: A cross sectional descriptive study. Duration of study: From October 2009 to January 2010. Setting: GTTH, Lahore. Subjects and Methods: All the nurses working in Ghurki T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
1
1
Order By: Relevance
“…The findings highlighted the primary importance of external motivation in selecting nursing as a career. This is in contrast to the results of a study by Manzour et al, which found that most participants considered personal interest as having the most significant impact on career choice (Manzoor et al, 2010). In this study, the two factors "recommendations from others (family, friends, and teachers)" and "media (television, Internet, and social networks)" earned the highest and lowest coefficients for importance, respectively, under the external motivation criterion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings highlighted the primary importance of external motivation in selecting nursing as a career. This is in contrast to the results of a study by Manzour et al, which found that most participants considered personal interest as having the most significant impact on career choice (Manzoor et al, 2010). In this study, the two factors "recommendations from others (family, friends, and teachers)" and "media (television, Internet, and social networks)" earned the highest and lowest coefficients for importance, respectively, under the external motivation criterion.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the two factors "recommendations from others (family, friends, and teachers)" and "media (television, Internet, and social networks)" earned the highest and lowest coefficients for importance, respectively, under the external motivation criterion. Similar external factors such as parental recommendations (Lim & Muhtar, 2016;Wu et al, 2015), employment of a family member in the profession (Manzoor et al, 2010), and the influence of others' suggestions and encouragement (Crawford & Turvey, 2019;Mooney et al, 2008) have been identified in other related studies as considerations in choosing a career in nursing. Given that family, friends, and teachers are important influencers in a person's life, their role in a future job search may be expected to be crucial and significant (Mphahlele, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, 68 second-year undergraduate nursing students who participated in a survey discovered that family members who work in the medical field were viewed as effective sources of both emotional support and practical assistance (Mclaughlin et al, 2010). However, other investigations carried out in Pakistan and India discovered the reverse (Patidar et al, 2011;Manzoor et al, 2010).…”
Section: Discussionmentioning
confidence: 99%